16 Aberrant emotional memory encoding in a transdiagnostic sample of patients with intrusive memories. Issue 12 (14th November 2022) - Smith, Alicia J; Bisby, James A; Dercon, Quentin; Bevan, Anna; Dalgleish, Tim; Hitchcock, Caitlin; Nord, Camilla
Abstract : Emotion can affect the way in which experiences are stored in our memory. The dual representation account proposes that traumatic events may be encoded as fragmented sensory-perceptual details without a broader conceptual organisation. This can result in involuntary retrieval of perceptual information triggered by environmental cues without the associated context – a phenomenon referred to as intrusive memories. Currently, it is unknown whether individuals who experience intrusive memories have an underlying vulnerability to aberrant memory encoding, which may lead to the onset or maintenance of symptoms. In Experiment 1, we examined memory recall for neutral and negative images in a transdiagnostic sample of patients with intrusive memories ( N = 36), compared to healthy controls ( N = 44). Clinical diagnoses in the patient sample included Post-Traumatic Stress Disorder, Major Depressive Disorder, Social Anxiety Disorder, Generalised Anxiety Disorder, Panic Disorder and Other Specified Feeding or Eating Disorders. We excluded participants currently taking psychotropic medication. At encoding, participants viewed neutral, negative and mixed valence image pairs. In the test phase, participants were presented with cues and, if recognised, were asked to recall the associated image. We found a significant group effect, with patients demonstrating impaired item memory for negative images [F(1, 280) = 4.435, p = 0.036], relative to healthy controls. This group difference might suggest that individuals with intrusive memories experienced greater sensitivity to negative stimuli, leading to disruptions in memory encoding. Recent work highlights attention maintenance on threat and high levels of threat-related emotional arousal in anxiety- and fear-related disorders which may be one factor driving the disruption to item memory observed in our clinical population. For Experiment 2, in a separate sample of healthy participants ( N = 18) we measured eye-tracking behaviour during the encoding phase of the same task. Healthy participants showed greater item memory [F(3, 136 = 2.893, p = 0.0377] and avoidance of fixation [F(1, 110) = 4.898, p = 0.029] on highly arousing, negative stimuli relative to neutral. This might suggest that a shift in attention away from negative stimuli prevents item memory impairments for emotional information. Our future work will identify biological factors driving attentional biases and higher emotional arousal in clinical populations.